Implementation of tariff rate quotas in the Philippines - Manzo, Preceles Hernandez (ProQuest Information and Learning Company, 2007)
Tariff rate quotas (TRQs) are one of the most widely used trade policy instruments in agricultural trade. The issue of whether TRQs are efficient trade policy instruments for improving market access has been widely debated. Some believe that TRQs impose an extra barrier to trade, circumvent the reforms sought under the General Agreement on Tariffs and Trade (GATT) and World Trade Organization (WTO) and may not be as attractive as initially envisioned. Others believe that the TRQs are useful and facilitate trade and liberalization. Any expansion in quota, or decrease in tariffs, or combinations of the two, has the potential to liberalize trade in a specific industry. There is strong clamor for continued reforms in the conduct of agricultural trade -- including the implementation of TRQs. The purpose of this study is to increase the understanding of TRQs, and determine the impact of their implementation on the Philippine corn market. Specifically, the study will estimate the quantities of supply, demand, imports, domestic equilibrium prices, and border prices under different TRQ liberalization regimes. In this study, an existing TRQ model was utilized to determine how effective TRQs are as a trade policy instrument for trade liberalization and increasing market access. The results reveal that the Philippine corn market was restricted by the out-quota tariff. De facto liberalization of the TRQ at the level of the out-quota rate (50%) or even at 35% (in-quota rate), does not completely liberalize the corn market. Progressively reducing both tariffs liberalizes the market and leads to increases in surpluses. The lower tariffs, however, lead to less government revenues. The smaller the gap between the in-quota and out-quota, the smaller the quota rents become. Increasing the quotas has no significant impact in liberalizing the corn market, and the increase in imports decrease producer surplus in all cases. The TRQ model of the Philippine corn sector reveals that changing the components of the TRQ would lead to different impacts on supply, demand, consumer, producer and net surplus, and government revenues. Knowledge of the regime in which the country is trading can determine which individual policy instrument of the TRQ, the in-quota and out-quota tariff and the quota, should be used to increase market access or address the concerns of stakeholders in the corn sector. It is thus important for policy makers to find a workable tariff level that would serve the interest of all stakeholders in the sector.--Abstract.